Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Perilaku Orangtua tentang Pencegahan Resiko Kekambuhan Sesak Napas Asma Anak - Boediarsih Boediarsih; Istiana Nur Aini; Sawitry Sawitry (Poltekkes Kemenkes Semarang, 2020)
Background: Asthma is a chronic respiratory disease with an increasing prevalence in children and adults since the last two decades. So that it becomes the cause of morbidity and mortality. Purpose: To analyze the effect of health education on knowledge and behavior of parents about preventing the risk of recurrence of asthma in children in Balkesmas, Ambarawa Region.Methods: The research used was quantitative descriptive with purposive sampling technique. The population of this study was 64 samples with health education intervention and analyzed to determine the effect of the research results.Results: Based on an analysis using the Wilcoxon signed rank test obtained p value is worth 0.000 (0.05), it can be concluded that there are changes in knowledge and behavior before and after in doing health education measures. There is an effect of health education with the knowledge of the parents of children with asthma with a p value of 0.000. There is an effect of health education on the behavior of the parents of children with asthma with a p value of 0.000.Conclusion: It is hoped that the results of this study can be used as a method of preventing recurrence of child asthma shortness of breath, by providing health education to parentsthus reducing dependence on drugs.